Adult mangrove stand does not reflect the dispersal potential of mangrove propagules: Case study of small islets in Lampung, Sumatra - AGUNG SEDAYU; NOVITA FARAH ISYADINYATI; DIANA VIVANTI SIGIT (Smujo International, 2012)
Abstract. Sedayu A, Isyadinyati NF, Sigit DV. 2011. Adult mangrove stand does not reflect the dispersal potential of mangrove propagules: Case study of small islets in Lampung, Sumatra. Nusantara Bioscience 4: 57-61. Most mangrove species are dispersed by water current with distance being a major constraint. We tried to demonstrate that distance is indeed the dispersal limiting factor in mangrove, and perhaps other marine plant species. Secondly, we also tried to clarify whether landmass is a real blockade for mangrove dispersal. Lastly, we argued that in order to study plant dispersal potential, one should not study the later stage of plant population, as normally plant ecologist would do, rather at their early life stage. Cluster analyses were used to test those hypotheses and confirmed our research hypotheses.